Practice Guidelines for Assisting Students with Visual Impairments - Eseadi, Chiedu (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
Students who are visually impaired but receive adequate support at an early stage have a greater chance of progressing in their academics and future careers. In this research article, the author identified various practice guidelines that can help students with visual impairments achieve a successful transition into the world of work. To discuss available practice guidelines for students from this population, the author conducted a narrative-integrative literature review. According to the study findings, teachers and schools have practical roles to play in assessing and administering educational programs for these students, as well as in utilizing assistive technologies. Further, the study provided guidelines for encouraging career transitions among these students, what is expected of their parents and caregivers, how to provide social and emotional support to these students, and ways to improve their access to library resources. This research contributes to advancing teachers', parents', librarians', and counsellors' knowledge about how to best assist students with visual impairments The study concluded that ongoing training is critical for all relevant stakeholders, including school administrators, parents, and teachers of visually impaired students.Siswa tunanetra yang menerima dukungan memadai pada tahap awal memiliki peluang lebih besar untuk maju dalam bidang akademik dan karir dimasa depan. Dalam artikel penelitian ini, penulis mengidentifikasi berbagai pedoman praktik yang dapat membantu siswa tunanetra mencapai transisi yang sukses ke dunia kerja. Untuk mendiskusikan pedoman praktik yang tersedia bagi siswa dari populasi ini, penulis melakukan tinjauan literatur naratif-integratif. Berdasarkan temuan penelitian, guru dan sekolah memiliki peran praktis dalam menilai dan mengelola program pendidikan bagi siswa tersebut, serta dalam menggunakan bantuan teknologi. Lebih lanjut, penelitian ini memberikan pedoman untuk mendorong transisi karir di kalangan siswa, apa yang diharapkan dari orang tua dan pengasuh mereka, bagaimana memberikan dukungan sosial dan emosional kepada siswa, dan cara untuk meningkatkan akses mereka terhadap sumber daya perpustakaan. Penelitian ini berkontribusi untuk meningkatkan pengetahuan guru, orang tua, pustakawan, dan konselor tentang cara terbaik untuk membantu siswa tunanetra. Studi ini menyimpulkan bahwa pelatihan berkelanjutan sangat penting bagi semua pemangku kepentingan terkait, termasuk administrator sekolah, orang tua, dan guru tuna netra.